The survival and growth of adult and juvenile hard clam Meretrix meretrix exposed to variable estuarine salinities in aquarium settings (Research in Agriculture Livestock and Fisheries, 2024)
Salinity fluctuations in estuaries can significantly impact marine organisms, leading to economic losses through mass mortalities of commercially important species. The effects of varying estuarine salinities on the survival, daily mortality, and growth of adult and juvenile hard clam Meretrix meretrix under controlled aquarium conditions were investigated. Adults (shell length ~45 mm) and juveniles (shell length ~30 mm) were collected from an 18 ppt estuarine habitat in Chowfaldondi, southeast Bangladesh, and exposed to six salinity levels (10, 15, 20, 25, 30, and 35 ppt) with three replications at ambient temperature. Adults were monitored for 51 days and juveniles for 23 days. Survival was significantly higher (≥80%) at 15–30 ppt for adults and 10–20 ppt for juveniles, with the lowest survival at 35 ppt. Analysis of co-variance showed that salinity had a greater effect on survival than the combined salinity*size model (p